1981
DOI: 10.1021/jm00140a014
|View full text |Cite
|
Sign up to set email alerts
|

N-Hydroxyacetaminophen: a postulated toxic metabolite of acetaminophen

Abstract: The decomposition of N-hydroxyacetaminophen has been shown to occur via an initial first-order dehydration step to N-acetyl-p-benzoquinone imine with a rate constant at pH 7.6 of 8.66 x 10(-3) min-1 and a half-life of 80 min. This is followed by a complex reaction between the quinone imine and the N-hydroxy compound to ultimately yield p-nitrosophenol and acetaminophen. The glucuronide and sulfate conjugates of N-hydroxyacetaminophen have been observed as urinary metabolites of N-hydroxyacetaminophen. No N-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…However, even in the LS pathway, the energy barrier of 29.6 kcal/mol (PCM) for the FeO oxygen addition to the PAR anilide nitrogen is too large to contribute significantly to the P450-catalyzed NAPQI formation. The latter may also explain the lack of reports of N-hydroxy-PAR 4 (with a half-life of 15 min) 35 as a metabolic precursor of NAPQI. Accordingly, the OAR mechanism also does not offer a kinetically efficient way for the metabolic conversion of PAR to NAPQI.…”
Section: ■ Computational Methodologymentioning
confidence: 99%
“…However, even in the LS pathway, the energy barrier of 29.6 kcal/mol (PCM) for the FeO oxygen addition to the PAR anilide nitrogen is too large to contribute significantly to the P450-catalyzed NAPQI formation. The latter may also explain the lack of reports of N-hydroxy-PAR 4 (with a half-life of 15 min) 35 as a metabolic precursor of NAPQI. Accordingly, the OAR mechanism also does not offer a kinetically efficient way for the metabolic conversion of PAR to NAPQI.…”
Section: ■ Computational Methodologymentioning
confidence: 99%
“…Initially, the formation of the arylating metabolite was believed to involve N-oxidation of acetaminophen to N-hydroxyacetaminophen followed by dehydration to N-acetyl-p-benzoquinone imine (NAPQI) (4). However, subsequent kinetic studies and carrier pool trapping experiments in vitro (5,6) and metabolism studies of N-hydroxyacetaminophen in vivo (7) have shown that if N-hydroxyacetaminophen is an intermediate, it must decompose at the enzymatic site of hydroxylation.…”
mentioning
confidence: 99%
“…We recently synthesized NAPQI in pure crystalline form, and studies have shown this reactive quinoneimine to be highly toxic in mice and to isolated hepatocytes (8). Other investigators, using aqueous solutions of NAPQI generated either electrochemically (9) or by dehydration of N-hydroxyacetaminophen (7,10,11), have shown NAPQI to be an electrophile and an oxidant. Similar properties were exhibited by stable benzene solutions of chemically synthesized NAPQI (12).…”
mentioning
confidence: 99%
“…This mechanism was subsequently modified following reports by Dr. Ian Calder's laboratory in Australia that N-acetyl-p-benzoquinone imine (NAPQI) was an electrophilic species (Calder et al 1973;Calder et al 1974;Calder et al 1981). They were able to synthesize it by oxidation with lead tetra-acetate, but it rapidly decomposed.…”
Section: Studies On the Mechanism Of Metabolic Activationmentioning
confidence: 99%